ANALISIS NILAI–NILAI PENDIDIKAN KARAKTER PADA NOVEL SELEMBAR ITU BERARTI KARYA SURYAMAN AMOPRIONO: Analysis of Character Education Values in The Novel Selembar Itu Berarti by Suryaman Amopriono - Isa, Nurul Farhah M; Saleh, Muhammad; Usman (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to describe the forms of character education values in the novel Selembar Itu Berarti by Suryaman Amopriono and the strategies for instilling character education values in the novel Selembar Itu Berarti by Suryaman Amopriono. The research data consists of texts containing character education values. The data sources that are the objects of this study are the values in the novel Selembar Itu Berarti by Suryaman Amopriono, namely honesty, discipline, creativity, social awareness, responsibility, democracy, religiosity, curiosity, hard work, independence, patriotism, appreciation of achievement, friendliness/communicativeness, love of reading, and love of peace. There are four strategies for instilling character education values in the novel Selembar Itu Berarti by Suryaman Amopriono. The results of this study indicate that there are forms of character education for character education values in the novel Selembar Itu Berarti by Suryaman Amopriono, namely the role model strategy, the advice strategy, the knowing goodness strategy, and the habit-forming strategy.